Perkembangan Prakelahiran dan Makna Kelahiran dalam Perspektif Al-Qur’an, Hadis, Medis Modern, dan Psikologi Perkembangan - Muhammad Haeril Jufri; Besse Mutmainnah*; Indo Santalia (Kartika: Jurnal Studi Keislaman, 2026)
This article discusses human development in the prenatal period and the meaning of birth as an integral part of the process of human formation from the early stages of life through an interdisciplinary approach that integrates Islamic perspectives, modern medicine, and developmental psychology. This research uses a descriptive qualitative approach with a literature study method sourced from the Qur'an, Hadith, classical and contemporary interpretations, as well as various relevant scientific publications. The results of the study show that in the Islamic view, human development has begun from the early stages of fetal formation and includes the spiritual, moral, and parental responsibilities dimensions. Meanwhile, findings in the field of medicine and developmental psychology confirm that biological factors, emotional conditions, and the mother's environment during pregnancy have a significant effect on the physical, neurological, and emotional development of children. Birth is understood not only as a biological event, but as an important transitional phase that continues the process of human development that has been going on since the prenatal period. The integration of these three perspectives confirms that human development needs to be understood comprehensively as a continuous process that involves biological, psychological, and spiritual aspects from the beginning of life.